Surgical Outcome if Laminectomy for Cervical Spondylotic Myelopathy - Sami, Ari (Sulaimani Journal for Pure and Applied Sciences, 2007)
Spondylotic myelopathy is a common spinal cord disorder encountered frequently by neurosuregeons. It can produce a variety of clinical signs and symptoms secondary to neural compromise and biomechanical involvement of the spine. The surgical approach depends on patient's age, the presence of spinal instability, and the pathology of compression. The surgical treatment is still debatable, anterior and posterior approaches have been used with various reported success rates. Thirty consecutive patients with cervical spondylotic myelopathy (CSM) were studied retrospectively. They had extensive laminectomy for the affected levels. The early result of surgical treatment was evaluated. Patient's age ranged between 27 and 70 years (mean 47.8 years). Males constituted %83.3 of the patients. The higher incidence was in the 5th and 6th decades. Limb weakness was the main presenting symptom. The duration of the deterioration of the neurological condition ranged from 1 month t0 2.5 years, with a mean of 6 months. Twenty six patients (%86.7) ahd some degree of improvement post-operatively, Severe radiculopathy (11 patients), wound infection (2 patients), and CSF collection (1 patient) were the main complications. There was no mortality, Although decompressive laminectomy is an indirect procedure in patients with anteriorly located lesions, like osteophytes and herniated discs, it is an effective method to relieve or arrest the progression of myelopathy, Best outcome was associated with shorter duration of symptoms prior to surgery, younger age, and good general condition.
Keywords: Cervical spodylosis; cervical myelopathy; Laminectomy; Radiculopathy; Laminoplasty